Cross compatibility of domesticated hot pepper and cultivated sweet pepper - Lucifrancy Vilagelim Costa; Ricardo Lopes; Maria Teresa Gomes Lopes; Antenor Francisco de Figueiredo; Willian Silva Barros; Silfran Rogério Marialva Alves (Crop Breeding and Applied Biotechnology, 2009)
This study evaluated the compatibility of crosses between C. chinense and C. annuum and the seed vigor andgermination of interspecific hybrids. Twenty-one accessions of C. chinense, used as male parents, were crossed with thecultivar Cascadura Ikeda (C. annuum) as female parent in a completely randomized design (CRD), with three replications.Fruit setting was evaluated in 30 flowers per plot. Seed germination and hybrid vigor were analyzed using CRD with fourreplications and plots of 16 seeds. All interspecific crosses produced fruit, at fruit set rates between 8.9% and 40.0%. In a firstcount, germination ranged from 0.0% to 45.3% and in the second from 0.0% to 87.5%. The conclusion was drawn that it ispossible to obtain fruit and viable seeds in interspecific crosses of C. chinense with C. annuum.